Penerapan Aplikasi Fruity Loops sebagai Media Pembelajaran Penciptaan Komposisi dan Aransemen Tata Suara - Laksono, Yunanto Tri (Faculty of Communications Science, Dr. Soetomo University, 2017)
The software is one of the essential tools in the learning process used in the modern era today, both for the improvement of technology and as a medium of learning. Fruity Loops is one of the learning media based on digital technology in the form of software used in writing and creating works or arrangements on the art of music in the way of partitions and audio. The structure of the creation of compositions and arrangements is an essential part of the art of music, mostly the value of harmonization created and felt in developing creativity in the art of music. Several things play a crucial role in the planning of the arrangement and composition, namely: (a) the form of musical composition, (b) primary ideas, (c) concepts, (d) patterns and methods of arrangement, (e) musical works. DIV Computer Multimedia at Stikom Surabaya which is the object of this research is one of the study programs which focus on film, television, and animation, so the purpose of learning through Fruity Loops is to develop the concept of sound in animation and film, and videos are original and do not violate copyright ethics, and serve as an introduction to learning based on Communication Technology.